2019
DOI: 10.1093/ajcn/nqy358
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt improves insulin resistance and liver fat in obese women with nonalcoholic fatty liver disease and metabolic syndrome: a randomized controlled trial

Abstract: Background Because consumption of conventional yogurt has beneficial effects in a healthy population, and insulin resistance (IR) is the mutual pathogenesis in nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome (MetS), we hypothesized that yogurt would ameliorate IR in patients with NAFLD and MetS. Objectives The aim of this study was to investigate the effects of yogurt on IR and secondary endpoints including li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 47 publications
2
67
1
Order By: Relevance
“…Furthermore, in patients with type 2 diabetes, the consumption of a probiotic yogurt containing 3.7 × 10 6 CFU/g of both L. acidophilus (La5) and B. lactic (Bb12), significantly decreased TNF levels (Mohamadshahi et al, 2014). A significant decrease in TNF levels, as a result of yogurt consumption, was also found in a RCT promoted by Chen et al, conducted in obese women with nonalcoholic fatty liver disease and metabolic syndrome (Chen et al, 2019). In this study conventional yogurt was used and a significant decrease in serum lipopolysaccharide (LPS), a biomarker of gut permeability, was also found as well as changes in GM composition, namely a decrease in the abundance of the Firmicutes phylum and the taxa within it (Chen et al, 2019).…”
Section: Fermented Foods As a Possible Alternative To Probiotic Supplementssupporting
confidence: 54%
“…Furthermore, in patients with type 2 diabetes, the consumption of a probiotic yogurt containing 3.7 × 10 6 CFU/g of both L. acidophilus (La5) and B. lactic (Bb12), significantly decreased TNF levels (Mohamadshahi et al, 2014). A significant decrease in TNF levels, as a result of yogurt consumption, was also found in a RCT promoted by Chen et al, conducted in obese women with nonalcoholic fatty liver disease and metabolic syndrome (Chen et al, 2019). In this study conventional yogurt was used and a significant decrease in serum lipopolysaccharide (LPS), a biomarker of gut permeability, was also found as well as changes in GM composition, namely a decrease in the abundance of the Firmicutes phylum and the taxa within it (Chen et al, 2019).…”
Section: Fermented Foods As a Possible Alternative To Probiotic Supplementssupporting
confidence: 54%
“…Yoghurt appears to be particularly beneficial in the prophylaxis of insulin resistance in women. A study by Chen et al [25] revealed that full-fat yoghurt significantly reduced HOMA-IR, fasting insulin levels and a 75 g 2 h oral glucose tolerance test compared to full-fat milk in women with metabolic syndrome and nonalcoholic fatty liver disease. However, the study showed significantly reduced HOMA-IR, fasting glucose and insulin levels in a group of women consuming milk, while the level of insulin in a 75 g 2 h oral glucose tolerance test significantly increased.…”
Section: Dairy Products and Insulin Resistancementioning
confidence: 99%
“…In the same study, an increase in butyrateproducing metagenomic species was described as well as a decrease of the pathobiont Bilophila wadsorthia implying that fermented dairy product consumption may result in modi cations of the composition but also the metabolic activity of the gut microbiota [16]. More recently in a 24-week intervention conducted in obese women with NAFLD and MetX, yoghurt consumption improved insulin resistance and changed the abundance of some members of Firmicutes compared to milk [6]. Thus, part of the bene cial effects of fermented milk product including yoghurt are thought to be mediated via modulation of the gut ecosystem.…”
Section: Introductionmentioning
confidence: 86%
“…Yoghurt consumption is associated with reduced body weight gain and incidence of type 2 diabetes in epidemiological studies [3][4][5]. Randomized controlled trials have shown that yoghurt intake reduces body fat in obese subjects and insulin resistance in obese women with nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome (MetX) [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation